EFISIENSI USAHATANI PADI BERAS HITAM DI KABUPATEN KARANGANYAR - Putra, Arya Senna; Setyowati, Nuning; Ani, Susi Wuri (Universitas Sebelas Maret, 2016)
The aim of this research were to analyze the revenue and the efficiency of black rice paddy farming in Karanganyar regency. The basic method of this research was descriptive analytic method. Location of the research was determined by purposive sampling in Karanganyar regency (census method). The number of black rice paddy farmers in Karanganyar regency was 23 people. Data used in the study were primary data as the main data and secondary data as supporting data. Data collected by observation, interview and record keeping. The results showed that black rice paddy farming in Karanganyar regency obtain the average revenue of IDR 8,974,565.22. Black rice paddy farming in Karanganyar regency were categorized efficient farming based on the average value of R/C Ratio were 2.84.